2006
DOI: 10.1160/th05-08-0571
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein, interleukin-6 and tumor necrosis factor alpha as predictors of incident coronary and cardiovascular events and total mortality

Abstract: Previous studies have shown an association between serum C-reactive protein (CRP) and cardiovascular disease (CVD) risk. The roles of interleukin-6 (IL-6) and tumor necrosis factor alpha (TNFalpha) are less well established. The aim of the present study was to analyze the associations of CRP, IL-6 and TNFalpha with incident coronary heart disease (CHD) events, CVD events, and total mortality. A random population sample, including men and women aged 25-64 years was examined in Finland in 1992. The sample size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
3
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(119 citation statements)
references
References 49 publications
9
102
3
5
Order By: Relevance
“…They reported that IL-6 was positively associated with an increased risk of all-cause and cardiovascular mortality (11). Contrary to that study, Tuomisto et al (12) reported that CRP and TNF-α, but not IL-6, were significant independent predictors of total mortality among men. Volpato et al reported that high IL-6 levels strongly affected the risk of mortality associated with the presence of CAD (13).…”
Section: Discussionmentioning
confidence: 90%
“…They reported that IL-6 was positively associated with an increased risk of all-cause and cardiovascular mortality (11). Contrary to that study, Tuomisto et al (12) reported that CRP and TNF-α, but not IL-6, were significant independent predictors of total mortality among men. Volpato et al reported that high IL-6 levels strongly affected the risk of mortality associated with the presence of CAD (13).…”
Section: Discussionmentioning
confidence: 90%
“…19 The same high-sensitivity C-reactive protein threshold (> 3 mg/L) has also been used to predict survival in noncancer cohorts. 20,21 Taken together, the results would suggest that a C-reactive protein level of 3 mg/L is a potentially significant threshold in both cancer and noncancer cohorts. It raises the possibility that inflammationbased prognostic scores such as those examined herein will have prognostic value in noncancer cohorts.…”
Section: Optimization Of the Gps/proctor Et Almentioning
confidence: 86%
“…Increased levels of the acute phase protein C-reactive protein (CRP), and the proinflammatory cytokines interleukin (IL)-6 and IL-18 were found to be associated with the risk of coronary heart disease (CHD; Blankenberg et al, 2003;Koenig et al, 2006;Kaptoge et al, 2010;Rodondi et al, 2010), death from CHD (Heidema et al, 2009) and all-cause mortality (Stork et al, 2006;Tuomisto et al, 2006;Jylha et al, 2007). In addition, single food components have been found to be related to inflammatory markers; higher intakes of dietary fibre (Ma et al, 2008;Herder et al, 2009;Wannamethee et al, 2009), whole-grain products (Qi et al, 2006;Lutsey et al, 2007), fruit and vegetables (Wannamethee et al, 2006;Holt et al, 2009), nuts (Salas-Salvado et al, 2008;Casas-Agustench et al, 2010), and a moderate alcohol intake (Wang et al, 2008;Oliveira et al, 2010) were associated with lower concentrations of several immune mediators in the circulation.…”
Section: Introductionmentioning
confidence: 99%